2000
DOI: 10.1021/ma9916382
|View full text |Cite
|
Sign up to set email alerts
|

Transesterification in Mixtures of Poly(ethylene terephthalate) and Poly(ethylene naphthalene-2,6-dicarboxylate):  An NMR Study of Kinetics and End Group Effects

Abstract: Mixtures of poly(ethylene terephthalate) and poly(ethylene naphthalene-2,6-dicarboxylate) have been transesterified at temperatures between 553 and 573 K. The partially transesterified polymers were analyzed using 1 H NMR, and the rate constants for transesterification were obtained using a kinetic expression based on a second-order reversible reaction mechanism. The hydroxyl end groups have been shown to have a significant effect on the kinetics of the reaction by comparing rate constants obtained for the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 8 publications
2
44
0
Order By: Relevance
“…The ester interchange reactions between PET and PCL gave a result similar to PET and PEN blend systems. [16][17][18] On the other hand, if ester interchange in the PET/PCL blend is only done by direct transesterification, the degree of ester interchange reactions should be identical because the population of ester groups in the blends is the same regardless of the MW of PCL at given composition. In fact, however, the degree of ester interchange reactions in PET/PCL blends is influenced by the MW of PCL.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ester interchange reactions between PET and PCL gave a result similar to PET and PEN blend systems. [16][17][18] On the other hand, if ester interchange in the PET/PCL blend is only done by direct transesterification, the degree of ester interchange reactions should be identical because the population of ester groups in the blends is the same regardless of the MW of PCL at given composition. In fact, however, the degree of ester interchange reactions in PET/PCL blends is influenced by the MW of PCL.…”
Section: Measurementsmentioning
confidence: 99%
“…Recently, it is reconfirmed the fact that the importance of the role of alcoholysis by hydroxyl end group via the control of molecular weight (MW) of PET in the kinetics of the ester interchange reactions between PET and poly(ethylene naphthalene-2,6-dicarboxylate) (PEN). [16][17][18] Taking into account the aforementioned reports, one of the possible solutions for the problems in melt blending of PET and PCL may be the control of the MW of PCL component. Thus, lower MW of PCL component can lead to higher degree of ester interchange reactions in short blending time because it increases the concentration of hydroxyl end group as presented in Figure 1.…”
mentioning
confidence: 99%
“…It was suggested that interchange reactions analogous to those in polyester [3,4,17] and polyamide [18] systems may occur in case of the eight-membered disulfide monomer, 2-methyl-7-methylene-1,5-dithiacyclooctane (MDTO). [13] The idea of these interchange reactions was put forward based on the finding of bimodal MWDs, which were speculated to originate from backbiting via addition of the propagating sulfur radical species to one of the double bonds on the polymer backbone, with subsequent b-fragmentation (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…To this aim, they examine whether the rate constant (extracted from the above-mentioned kinetic equation for dyads) depends on the average MW of the initial blend components [9][10][11], study the interchange kinetics in blends of model compounds [12,13] or in polymer end-capped blends [14,15], or detect the difference in composition between the copolymer and the blend as a whole [16]. However, the results are not always easy to interpret, e.g., the discussion on the main interchange mechanism in the popular blend PET/PEN still lasts [13,14,17,18].…”
Section: Introductionmentioning
confidence: 99%